A high‐voltage gain nonisolated noncoupled inductor based multi‐input DC‐DC topology with reduced number of components for renewable energy systems. (29th November 2017) - Varesi, Kazem; Hosseini, Seyed Hossein; Sabahi, Mehran; Babaei, Ebrahim
Summary: This paper proposes a modular nonisolated noncoupled inductor‐based high‐voltage gain multi‐input DC‐DC converter. Despite the high‐voltage gain of the proposed topology, the average of normalized voltage stress (NVS) on its switches/diodes is low. This property leads to less loss and cost of switches/diodes. Using the same number of components, the proposed topology produces higher voltage gains, in comparison with recently presented high step‐up topologies. Also, the proposed topology utilizes less number of components (capacitors, inductors, diodes, and switches) for producing a desired voltage gain, which can reduce the size, mass, cost, complexity, and losses and improve the efficiency of converter. Continuous current of input sources is another main advantage of the proposed topology. All the abovementioned characteristics have made the proposed topology very suitable for renewable energy systems (or even hybrid/electric vehicles). Design considerations of the proposed topology have also been presented. For better evaluation, the proposed topology has been compared with some of recently presented high step‐up structures, from viewpoints of producible voltage gain, number of components, and normalized voltage stress (NVS) on switches/diodes. Finally, the prototype of 2‐input version has been experimentally implemented. Obtained experimental results confirm appropriate performance of the proposed topology. Abstract : This paper proposes a modular nonisolated noncoupled inductor‐based high‐voltage gain multi‐input DC‐DC converter, in which bidirectional capability has been provided. Despite the high‐voltage gain of the proposed topology, the average of normalized voltage stress (NVS) on switches/diodes is low, compared with recently presented high step‐up topologies. This property leads to less loss and cost of switches/diodes. The proposed topology uses less number of components (capacitors, inductors, diodes, and switches) for producing a desired voltage gain. In other words, for the same number of components and values of duty cycles, the proposed topology presents higher voltage gains, in comparison with recently presented high step‐up topologies. So, the proposed topology is expected to have less size, mass, cost, complexity and losses, and higher efficiencies. Continuous current of input sources is another main advantage of proposed topology. All abovementioned characteristics have made the proposed topology very suitable for renewable energy systems or even hybrid/electric vehicles.